2017
DOI: 10.1136/archdischild-2016-312276
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen-minute consultation: stabilisation of the high-risk newborn infant beside the mother

Abstract: Paediatric and adult resuscitation is often performed with family present. Current guidelines recommend deferred umbilical cord clamping as part of immediate neonatal care, requiring neonatal assessment next to the mother. This paper describes strategies for providing care beside the mother using both standard resuscitation equipment and a trolley designed for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…When a neonate in need of resuscitation is born, immediate clamping and cutting of the umbilical cord is still recommended according to several guidelines (see an overview in Supplement 1). Pilot studies have shown that resuscitation with an intact cord is a feasible practice for term non-vigorous vaginally born neonates, and data have shown there are long-term benefits during infancy [ 9 11 ]. Yet, larger randomized control trials are needed to supply reliable evidence regarding the appropriate steps to be taken during intact cord resuscitation (ICR) [ 3 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…When a neonate in need of resuscitation is born, immediate clamping and cutting of the umbilical cord is still recommended according to several guidelines (see an overview in Supplement 1). Pilot studies have shown that resuscitation with an intact cord is a feasible practice for term non-vigorous vaginally born neonates, and data have shown there are long-term benefits during infancy [ 9 11 ]. Yet, larger randomized control trials are needed to supply reliable evidence regarding the appropriate steps to be taken during intact cord resuscitation (ICR) [ 3 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches to intact-cord stabilization have also been proven feasible. Batey and colleagues [42] describe how intact-cord stabilization of high-risk infants can be done either with a standard resuscitation table or the LifeStart™ trolley. The Baby-DUCC feasibility study [37] is another example of how this may be done.…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential problem of overstretching or kinking the cord, represented by the one case of cord snapping when using mobile equipment, is a safety issue that needs to be addressed. Other researchers have also described this challenge, and how it can be overcome, for example by placing the trolley closest possible to the birth canal [37,42].…”
Section: Safety Issuesmentioning
confidence: 99%
“…Strengths of our trial were that clamping was deferred for longer than in other trials at very preterm birth and that immediate neonatal care (including stabilisation and resuscitation), if needed, was provided with the cord intact. 20 Providing neonatal care with the cord intact allowed high-risk babies needing immediate resuscitation at birth to be randomised, a group largely excluded from previous trials. 21 …”
Section: Discussionmentioning
confidence: 99%